Empowerment for Education of Students with Special Education Needs - Audronė Dumčienė; Saulius Šukys (Lithuanian Sports University, 2018)
Background. Teachers who are in favour of education of students with special needs (SEN) together with their peers (inclusive education) appreciate the role of parents in the education process of students. However, Čiuladienė and Paužienė (2012) indicate that the majority of Lithuanian general education schools are not sufficiently prepared for inclusive education. Methods. The sample consisted of 170 parents of students with SEN in grades 5-10. The scale of Parental Involvement in School was used to establish parental involvement in children's education process. Results. The parent involvement levels in children's education process were established using three five-point scales: Parent Involvement with Teacher/School - 1.60  points; Teacher Involvement with Parent - 2.22 points; Parent Involvement with Child's Schoolwork - 3.03 points. More educated parents compared to parents with lower education indicated that communicating with teachers they really felt equal partners (χ 2  = 20.37, p < .001). Parents admit that better collaboration between parents and teachers can more encourage open and honest communication  between  them  (63.5%). A  little  less  than  three-quarters  of  parents  often  or  very  often  received information from teachers about their children's learning and behaviour. Parents who claimed to have sufficient knowledge of educating their children sometimes indicated that they needed teachers and other professionals to help them with their children's development problems (χ 2  = 14.11, p < .001). Conclusions. Most parents were involved in the education of pupils with SEN at home but they were little involved in their children's educational process at school and other school activities. Keywords: student, special education needs, parent, teacher.